Self-powered portable melt electrospinning for in situ wound dressing - Zhao, Ying-Tao (J Nanobiotechnology, 2020)
BACKGROUND: Electrospun (e-spun) nanofibers for wound dressing have attracted wide attention due to its large specific surface area, large porosity and breathability. Compared with solution electrospinning (e-spinning), melt e-spinning is more bio-friendly without toxic solvent participation, which provides the possibility of in situ e-spinning on wounds directly. However, previously reported melt e-spinning devices were usually bulky and cumbersome due to their necessary heating unit, and different components were separated to avoid electrostatic interference. RESULTS: In this article, we report on a self-powered hand-held melt e-spinning gun which can work without any external power supply (outdoors). The problem of electrostatic interference for this integrated device was solved by using a special high heat transfer insulation unit. The apparatus is easy and safe to operate by a single hand due to its small volume (24 × 6 × 13 cm(3)) and light weight (about 450 g). Some biodegradable polymers, for example, polycaprolactone (PCL) fibers were successful e-spun onto wounds directly by using this dressing gun. CONCLUSIONS: PCL fibrous membrane has good biocompatibility and can be in situ electrospun to wound surface as a wound dressing by the portable melt e-spinning gun. Besides wound dressing, this hand-held melt e-spinning gun may be used in 3D printing and experimental teaching demonstration aids.